Exploring self-declared prohibited substance use in combat sports: The Serbian perspective - Vuk Raonić; Ivana Milovanović; Roberto Roklicer; Marko Manojlović; Tatjana Trivić; Patrik Drid (Exercise and Quality of Life)
The exploratory study is grounded in field research, utilizing semi-structured interviews with active, former, and recreational athletes in combat sports. The first section outlines key theoretical frameworks that address everyday life, lifestyles, and the issue of doping. The second section presents the main findings from the field research. Interviewees detailed the positive effects of doping on athletic performance while also acknowledging significant side effects, including physical and psychological consequences. Participants highlighted that the availability of information on doping has increased with the advent of the Internet and specialized retail outlets. The testimonies indicate that the culture of doping is driven not only by the pursuit of enhanced sports performance but also by aesthetic considerations and social pressures, underscoring the complexity of doping use in both professional and recreational sports. The study concludes that doping is a pervasive issue in combat sports, necessitating comprehensive social action and collaboration among policymakers, social stakeholders, and researchers across multiple disciplines, with a prominent role for physical education and sports sciences.